Síndrome Doloroso Patelo-Femoral (SDPF) - Influência de Ortóteses Estabilizadoras Dinâmicas da Rótula em Atletas de Voleibol Feminino - Nuno Miguel Prucha Leite (2020)
Background: Patellofemoral Pain Syndrome (PFPS) is one of the most challenging diagnoses of knee pathology. It is a controversial and non-consensual entity regarding its pathophysiology, diagnosis and treatment. Currently, there is lack of evidence in the literature about the efficacy of dynamic stabilizing knee orthosis, specially Donjoy Performance Webtech(r) as a method of treating PFPS. Thus, this study aims to evaluate the biomechanical influence of the knee orthosis during the jumping movement in athletes diagnosed with PFPS. Methods: 11 female athletes with PFPS were instructed to perform the attack jump movement. Three valid repetitions were performed, with and without orthosis, for further processing in biomechanical analysis software. The following variables were evaluated: knee joint angle at maximal valgus moment of left knee and right knee, knee range of motion (ROM), ground reaction force components (FRS) during maximal knee valgus instant for the left knee and right knee, knee joint angle at maximum FRS and peak knee joint angle. Results: Results indicate that the joint movements become more similar between the left and the right knee with the use of the orthosis and that its use decreases the varus knee angle. In addition, with the use of the orthosis, we found that the knee ROM increases and that there is predominantly internal rotation of the knee during the studied movement. Conclusion: In conclusion, the results of this study suggest that the Donjoy Performance Webtech (r) knee orthosis may be an effective adjunct to kneecap stabilization in people with anterior knee pain.